PROBLEM ANALYSIS ON SHARIA PROPERTY BUSINESS AND ITS PROPOSED SOLUTION - Asep Bagja Nugraha; Raden Aswin Rahadi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Sharia concept is one of disruptive factors in current economic and business along with digital disruptive and millennial disruptive. Sharia concept has brought disruption with the increasing demand for halal products, sharia banking and economics, including sharia property. The increasing number of demands in sharia property product has attracted many property developers to create sharia-based property product. Unfortunately for the last three years (2019-2021), there were some cases reported to the police with accusations in fraud or undelivered project. With such kind of impact and potential, there must be anticipation to anticipate such condition. Problem analysis on sharia property business results in three main issues. They are lack of understanding in business related sharia law, lack of understanding on property business process, and marketing issue. Proposed solution for lack of understanding in business related sharia law is to review the basic principles of sharia business, sharia law regarding partnership (syirkah), sharia capital aspects, and sharia business transaction in the property business. Proposed solutions for lack of understanding in property business process are 9 steps to starting a sharia property business. And in the last issue regarding marketing aspect, the author suggests to optimize value proposition of sharia property product and maximize digital marketing strategy.